2007
DOI: 10.1167/iovs.06-1222
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Retinoic Acid Receptor Alpha Stimulants on Murine Cataractogenesis through Suppression of Deregulated Calpains

Abstract: Results showed that a certain type of RA inhibits Ca(2+) elevation and subsequent overactivation of calpains, suggesting the potential feasibility of calpain-targeting therapies mediated by RA for cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Retinoids suppress the differentiation of preadipocytes to adipocytes [28], and promote alveolar regeneration in mammalian lungs [29]. Other observations suggest several clinical potential applications such as the treatment of diabetic retinopathy [30] and cataract [31]. Animal experiments using non-obese diabetic (NOD) mice suggested that retinoids may be effective to suppress type I diabetes and Schoegren’s syndrome [32].…”
Section: Biological and Pharmacological Activities Of Retinoidsmentioning
confidence: 99%
“…Retinoids suppress the differentiation of preadipocytes to adipocytes [28], and promote alveolar regeneration in mammalian lungs [29]. Other observations suggest several clinical potential applications such as the treatment of diabetic retinopathy [30] and cataract [31]. Animal experiments using non-obese diabetic (NOD) mice suggested that retinoids may be effective to suppress type I diabetes and Schoegren’s syndrome [32].…”
Section: Biological and Pharmacological Activities Of Retinoidsmentioning
confidence: 99%
“…The cut-off levels in mice used to diagnose diabetes were more than 200 mg/dl in blood sugar measured using Gluco-card (ARKRAY, Kyoto, Japan) and positive urinal sugar measured using Rub-stick (Bayer, Leverkusen, Germany). Six weeks after the verification of diabetes, when the blood–retinal barrier breakdown was progressing as previously described (Nishikiori et al 2007a), mice were treated with 1.0 mg/kg ATRA every day (seven mice, 14 eyes) or 3.75 mg/kg Am580 every other day (nine mice, 18 eyes) for 1 week (Nishikiori et al 2007a, 2007b). Control mice (eight mice, 16 eyes) were i.p.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that stimulation of RARα decreased Ca2+ influx into the lens and reduced the over activation of calpains. RARα can potentially be used for prevention and treatment of human diabetic cataracts [23]. …”
Section: Nrs and Ocular Diseasesmentioning
confidence: 99%